Implementation of Scouting Extracurricular Activities during the Covid19 Pandemic Period: Implementasi Kegiatan Ekstrakurikuler Kepramukaan pada masa Pandemi Covid19 - Wahib Chasbullah; Ida Rindaningsih (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigated the implementation, advantages, and disadvantages of Scout Extracurricular Activities during the COVID-19 pandemic at SD Negeri Gebang 1 Kec. Sidoarjo. The research utilized qualitative descriptive methods, including interviews, observations, and analysis of school documentation. The findings revealed that the online system was the most effective alternative for conducting Scouting Extracurricular activities during the pandemic. The advantages of online scouting activities included efficiency, time and energy savings, flexibility in learning locations, relaxed student participation, and customizable learning settings. However, there were also drawbacks, such as unpreparedness of parents and students for online systems, the need for internet access, limited communication tools, suboptimal material delivery and reception, and time constraints. These findings highlight the importance of educators, students, and parents in adequately preparing for both online and offline learning models. Additionally, it emphasizes the need for innovative approaches, such as blended learning methods combining online and offline systems. Highlights: The implementation of Scout Extracurricular Activities during the COVID-19 pandemic at SD Negeri Gebang 1 Kec. Sidoarjo is carried out using an online system as the best alternative. Advantages of online scouting activities include efficiency, flexibility, and relaxed student participation. Disadvantages of online scouting activities include unpreparedness, limited access, and suboptimal material delivery. Keywords: Scout Extracurricular Activities, COVID-19 pandemic, Implementation, Advantages, Disadvantages